Community Empowerment At The Akehuda Digital Waste House To Support Circular Economy Activities In Ternate City - Raiqa Salsa Billah; Rizka Utama Putri; Abd Reza Wagas; Winny Zuhrita Adjaran; Ulma Makehe; Fahira Odemadi; Buhar Hamja; Hamidah Rahman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Accumulation of waste can cause environmental quality to decline, the emergence of unpleasant odors and pollution of land and water. Apart from that, plastic waste that is not thrown away in the trash can cause it to be thrown into the sea, as it happens in the sea surrounding Ternate Island. The waste management system must be carried out comprehensively, among the central government, regional government and the community, for example by establishing a digital waste house based on community empowerment activities. The aim of this activity is to improve community behavior in sorting waste at the household level so that the volume of waste reaching the landfill is reduced. Apart from that, it can increase people's knowledge and skills in managing waste businesses through the establishment of digital-based waste houses. The next goal is to improve community skills in processing inorganic waste and plastic waste as well as processing organic waste into compost fertilizer and various ecoenzyme derivative products. It is hoped that the results of the activity can initiate the formation of community entrepreneurship based on processed waste products to support circular economic activities. Activities were carried out from July to September 2023 located in Akehuda Village, Ternate City. The implementation method was socialization of waste management through counseling and at the same time assistance in processing waste. Apart from that, community empowerment was carried out by establishing a digital-based waste house. The results of the activity show that the partners already have a digital-based waste house, partner members were able to manage the waste processing business from the Marasai digital waste house, partner members have the knowledge and skills to process waste. In order to increase public interest and participation in processing waste, it is necessary to continue to carry out socialization about waste processing.